(untitled) (Andamios, Revista de Investigación Social, 2007)
The main idea expressed by Fernando Savater in his works in ethics on the subject of human rights is that, when we confront the question of to whom do we refer when we speak of human rights, to concrete, physical persons or to “collective persons,” that is to say corporations, the response is obvious: we are speaking of individual persons, because collective persons don´t exist.